Síntese de hidroxiapatita para aplicação em biocerâmicas: uma revisão da literatura - MONTEIRO, Maria Luiza da Silva (2021)
Predominantly present in bone tissue, hydroxyapatite can be synthesized in laboratories using several routes. Thus allowing to create a biomaterial similar to tissues found in the human body. Due to this similarity with the mineral phase of bones, hydroxyapatite is a material often used as a bioceramic for the formulation of implants, grafts and bone replacements. The study of hydroxyapatite synthesis is a very important line of research for science, making more and more frequent works involving the ptimization of the parameters of this process and the physical-chemical properties of this material. In the present work, a review of the literature regarding the synthesis of hydroxyapatite for application in bioceramics is carried out. This survey was based on the search for scientific papers, including theses, dissertations, monographs and articles published in the last five years. The study carried out on these synthesis routes confirmed the range of possibilities for using these processes and how optimization is possible to facilitate and make the production of this material even more efficient. The wet precipitation method is the most commonly used by scholars, however, it is worth emphasizing the viability of this material from “dry route” routes including the hydrothermal and sol-gel methods.